2014
DOI: 10.1186/1472-6963-14-398
|View full text |Cite
|
Sign up to set email alerts
|

Single item measures of self-rated mental health: a scoping review

Abstract: BackgroundA single-item measure of self-rated mental health (SRMH) is being used increasingly in health research and population health surveys. The item asks respondents to rate their mental health on a five-point scale from excellent to poor. This scoping study presents the first known review of the SRMH literature.MethodsElectronic databases of Medline, CINAHL, PsycINFO, EMBASE and Cochrane Reviews were searched using keywords. The databases were also searched using the titles of surveys known to include the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
297
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(304 citation statements)
references
References 62 publications
(68 reference statements)
4
297
1
2
Order By: Relevance
“…As discussed earlier, SPMH status and multi-items mental health screening scales (eg, K6, SF 12, PHQ-2) are associated but not interchangeable. 28 In its CCHS-Mental Health cycle 2012, Statistics Canada collected K6 data which was not associated with FOBT uptake. 35 While being male was an independent risk factor for CRC, 14,36 the current study findings suggest that men had slightly lower odds of screening compared to women in both crude and adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, SPMH status and multi-items mental health screening scales (eg, K6, SF 12, PHQ-2) are associated but not interchangeable. 28 In its CCHS-Mental Health cycle 2012, Statistics Canada collected K6 data which was not associated with FOBT uptake. 35 While being male was an independent risk factor for CRC, 14,36 the current study findings suggest that men had slightly lower odds of screening compared to women in both crude and adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that SPMH status is a "general indication of the number of people in the population suffering from some form of mental disorder, mental or emotional problems or distress, not necessarily reflected in self-perceived health, " and is associated with multiitems mental health scales such as K6 scale of psychological distress, mental health subscales of the SF-12 health status survey, and patient health questionnaire (PHQ-2) depression screener. 28 Self-reported health has also been shown to be highly correlated with overall health outcomes and can be considered to provide a valid measurement of mental health disorders. 29 Potential confounders included in the current analysis were age (5-year age groupings), gender (males vs. females), level of education completed (less than secondary education, secondary education, completion or vs. some/completed post-secondary education), race (White vs. non-White), and immigration status (yes vs. no).…”
Section: Study Variablesmentioning
confidence: 99%
“…[1][2][3][4][5] Following recommendation by the Institute of Medicine (IOM), single-item measures of SRH are being used as a tool to monitor the health of the US population. [6][7][8] Singleitem physical and mental SRH 9 predict a wide range of health outcomes, such as utilization of health care, 10,11 development of chronic medical conditions, 1,2,12-14 and mortality. 15 Perceived poor health (poor SRH) prompts a complex cognitive process that is required for health care utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of measurement soundness and clinical usefulness has been provided for single-item global ratings of a number of complex phenomena, including physical and mental health [5]. Specifically, a single item of perceived mental health rated on a 5-point scale was shown to be associated with multiple-item scales of mental health, physical health problems, and health service utilization [5].…”
mentioning
confidence: 99%